MEMO: Monitoring of exotic mosquitoes in Belgium - Isra Deblauwe; Dimitri Brosens; Katrien De Wolf; Nathalie Smitz; Adwine Vanslembrouck; Anna Schneider; Jacobus De Witte; Ingrid Verlé; Wouter Dekoninck; Marc De Meyer; Thierry Backeljau; Sophie Gombeer; et al. (GigaByte, 2022)
‘MEMO: Monitoring of Exotic MOsquitoes in Belgium’ is a sampling event dataset published by the Institute of Tropical Medicine (ITM) in Antwerp, Belgium. It forms part of the early detection of exotic mosquito species (EMS) along high-risk introduction routes in Belgium, where data are collected at defined points of entry (PoEs) using a standardised protocol. The MEMO dataset contains mosquito sampling counts performed between 2017 and 2020. MEMO+2020, an extension of the MEMO dataset, contains only Aedes albopictus mosquito trap counts performed in 2020. Here, we present these data published as a standardised Darwin Core archive, which includes, for each sampling event, an eventID, date, location and sampling protocol (in the event core); and an occurrenceID for each occurrence (tube), the number of collected individuals per tube, species status (present/absent), information on the identification and scientific name (in the occurrence extension).